Continuous Micro Liquid‐Liquid Extraction. Issue 6 (11th April 2013) - Assmann, N.; Ładosz, A.; Rudolf von Rohr, P.; Hessel, Volker; Wang, Qi
Abstract Among the different separation processes, liquid‐liquid extraction especially benefits from microfluidics as the short molecular diffusion distance and large specific interfacial area in microchannels are advantageous for effective liquid/liquid contacting. An overview is given on different examples of continuous micro liquid‐liquid extraction. As contacting of the two phases as well as phase separation strongly depend on the flow pattern, one chapter is devoted to each parallel flow, segmented flow, and emulsions. Advantages and disadvantages of the three flow patterns are compared to each other. Additionally, possibilities for scaling up microfluidic concepts for higher‐throughput systems are presented.